Benchmarking Approach to Compare Web Applications Static Analysis Tools Detecting OWASP Top Ten Security Vulnerabilities - Bermejo Higuera, Juan Ramón; Bermejo-Higuera, Javier; Sicilia, Juan Antonio; Cubo Villalba, Javier; Nombela Pérez, Juan José (CMC-Computers Materials & Continua, 2020)
To detect security vulnerabilities in a web application, the security analyst must choose the best performance Security Analysis Static Tool (SAST) in terms of discovering the greatest number of security vulnerabilities as possible. To compare static analysis tools for web applications, an adapted benchmark to the vulnerability categories included in the known standard Open Web Application Security Project (OWASP) Top Ten project is required. The information of the security effectiveness of a commercial static analysis tool is not usually a publicly accessible research and the state of the art on static security tool analyzers shows that the different design and implementation of those tools has different effectiveness rates in terms of security performance. Given the significant cost of commercial tools, this paper studies the performance of seven static tools using a new methodology proposal and a new benchmark designed for vulnerability categories included in the known standard OWASP Top Ten project. Thus, the practitioners will have more precise information to select the best tool using a benchmark adapted to the last versions of OWASP Top Ten project. The results of this work have been obtaining using widely acceptable metrics to classify them according to three different degree of web application criticality.
Keywords: web application; benchmark; security vulnerability; Security Analysis Static Tools; assessment methodology; false positive; false negative; precision; f-measure; JCR; Scopus